2010
DOI: 10.4317/medoral.15.e875
|View full text |Cite
|
Sign up to set email alerts
|

Social demand for oral surgery in third age patients and its association with systemic pathologies

Abstract: Objectives: To determine the frequency of systemic pathologies in patients aged 65 years or more, who require oral care and possibly oral surgery. Study Design: We carried out a cross-sectional descriptive study reviewing 3,388 medical histories for patients from the Department of Medicine and Oral Surgery of the School of Dentistry at the Complutense University of Madrid, who had requested surgical treatment. Those selected were at least 65 years of age or more, and were grouped according to their medical his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
2
1
0
Order By: Relevance
“…Out of them, 65,74% had diabetes, 25,92% hypothyroidism, 3,70% hyperthyroidism and the other 4,62% suffered from other type of endocrine disease. Similar to our study, other reviews report diabetes as the most common pathology among endocrine diseases ( 7 , 8 , 10 ). About 2% of the patients attending dental clinics suffer from diabetes, with about half of them unaware of their condition.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Out of them, 65,74% had diabetes, 25,92% hypothyroidism, 3,70% hyperthyroidism and the other 4,62% suffered from other type of endocrine disease. Similar to our study, other reviews report diabetes as the most common pathology among endocrine diseases ( 7 , 8 , 10 ). About 2% of the patients attending dental clinics suffer from diabetes, with about half of them unaware of their condition.…”
Section: Discussionsupporting
confidence: 92%
“…( 10 ) and Martinez-González et al . ( 8 ) also considered the HT as the most frequent pathology (44,9% and 40,5% respectively), although only patients over 65 were included. Our results are also compatible with the Spanish National Health Survey from 2011-2012 and also in the previous one from 2006, which stated that HT was the most prevalent chronic or long-standing problem or disease diagnosed by doctors in individuals over 15 years in Spain ( 11 , 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of systemic disease in patients in the study group was similar to that detected by other authors, both in patients from the public system ( 11 , 12 ) and in those from private practice ( 2 , 4 , 13 ). The majority of diseases were of cardiovascular origin, particularly systemic hypertension (HT), as reported in previous studies ( 4 , 6 , 12 - 15 ); this is compatible with the report of the National Health Survey from 2006 ( 16 ), which stated that HT was the most prevalent chronic or long-standing problem or disease diagnosed by doctors in individuals over 16 years of age in Spain. Fernández-Feijoo et al ( 17 ), in a screening study for HT performed in a public health system dental clinic, found that 29.2% of patients requesting dental treatment had blood pressure levels suggestive of HT.…”
Section: Discussionsupporting
confidence: 88%